Parental autonomy support and future education planning among Chinese senior high school students: a chain mediation model integrating self-determination theory and social cognitive theory - Liu, Guirong; Zhang, Mengyun; Zhang, Xiaomei; Yang, Guizhou; Wang, Feng; Zhang, Jinghuan; Teng, Xiuqin; Wang, Yan (Frontiers in Psychology, 2026)
IntroductionParental autonomy support (PAS) has been identified as a key factor in shaping adolescents’ educational development, yet little research has examined how PAS predicts students’ future educational planning (FEP) and whether this relationship is mediated by specific motivational mechanisms.MethodsDrawing on an integrative framework combining Self-Determination Theory (SDT) and Social Cognitive Theory (SCT), the present study investigated whether senior high school students’ basic psychological needs satisfaction (BPNS) and academic self-efficacy (ASE) sequentially mediate the relationship between PAS and FEP. A total of 1,591 Chinese senior high school students from three schools in Jinan, Shandong Province completed standardized measures of PAS, BPNS, ASE, and FEP.ResultsResults showed that PAS significantly predicted students’ FEP. BPNS alone mediated the relationship between PAS and FEP, and BPNS and ASE jointly served as significant chain mediators.DiscussionThese findings underscore the role of supportive parenting and internal motivational resources—namely, the satisfaction of basic psychological needs and efficacy beliefs—in facilitating adolescents’ engagement in future-oriented educational planning during high school. The study also advances theoretical understanding by integrating SDT and SCT to illuminate a hierarchical motivational pathway linking parenting practices to future planning outcomes.